Review on Resistance Force to Open Channel Flow through Emergent Vegetation (Journal of Academic Research, 2022)
In this study, the resistance force characteristics formed by emergent vegetation in open channel flow has been reviewed. In vegetated open channels, the total flow resistance is controlled by the combination of drag force caused by vegetation and bed shear force. Different approaches have been used to model the drag force caused by vegetation and roughness of channel bed. Conventional equations such as Manning’s equation or Darcy-Weisbach have been used to play an important rule to investigate these phenomena. Recent researches indicated that Manning’s equation should not be used when flow is relatively slow and channel depth is not constant. However, recently, new approaches such as Kármán Vortex Street or Large Eddies Simulation (LES) are utilized as flow interpreters through vegetation. Different vegetation arrangements (e.g., lined, staggered, grid, and random) were studied and different results were obtained in estimating the drag force and drag Coefficient (Cd) in the system. In general, Vegetation density and approach velocity are the characteristics that control the drag force amount exerted by vegetation.